Site, Adapt, Perform A Practice-as-Research Confrontation with Climate Change - Kloetzel, Melanie 1949- (Edinburgh: Edinburgh University Press, 2017)
RESUMEN: In recent years, art festivals around the globe have become enamoured of touring, site - based performance. Such serialised site work is growing in popularity due to its accessibility, its spectacular characteristics, and its adaptive qualities. Employing practice-as-research methodologies to dissect the basis of such site-adaptation performances, the author highlights her discovery of the crumbling foundation of the adaptation discourse by way of her creative process for the performance work Room. Combining finding from the phenomenological explorations of her dancing body as well as from cultural analyses of the climate change debate by Dipesh Chakrabarty (2009), Claire Colebrook (2011, 2012), and Bruno Latour (2014), the author argues that only by fundamentally shifting the direction of the adaptation discourse - on scales from global to the personal - will we be able to build a site-adaptive performance strategy that resist the neoliberal drive towards ecological and economic precarity. PALABRAS CLAVE: site-specific performance, adaptation, site-adaptive dance, climate change, precarity